Knockdown of Fibromodulin Inhibits Proliferation and Migration of RPE Cell via the VEGFR2-AKT Pathway. (12th September 2018) - Hu, He; Li, Shanshan; Li, Jianqiao; Huang, Chao; Zhou, Fang; Zhao, Li; Yu, Wenzhen; Qin, Xiao
Abstract : Purpose . Recent research has provided novel insight into the function of fibromodulin (FMOD) in wound healing and angiogenesis. The role of FMOD in initiation of proliferative vitreoretinopathy (PVR) has not been studied. This study investigated the effect of FMOD on human retinal pigment epithelial (RPE) cell, which plays an essential role in the progression of PVR, and the possible mechanisms. Methods . Small interfering (si) RNA-based gene transfer technology was used to decrease FMOD expression and to study its effects on RPEs in vitro . Cell Counting Kit-8 assays, transwells, and flow cytometry analysis were used to measure cell proliferation, migration, cell cycle, and apoptosis. Western blot was used to measure expression of vascular endothelial growth factor (VEGF), VEGF receptor 2 (VEGFR2), extracellular signal-related kinase 1/2 (ERK1/2), and phosphoinositide 3 kinase (PI3K/AKT). Results . After transfection of RPEs with a FMOD-specific siRNA, cell proliferation and migration were inhibited to the percentage of 65% ± 5% and 39% ± 10%, respectively, compared to the control group. Depletion of FMOD induced cell cycle arrest and apoptosis in RPE cells. Downregulation of VEGF, VEGFR2, and phosphorylated AKT (p-AKT) were detected in transfected RPEs. Conclusion . Depletion of FMOD selectively downregulated the expression of VEGF and VEGFR2 and inhibited the signaling pathway of AKT phosphorylation, which consequently inhibited the proliferation and migration of RPE Cell.